Analisa Pertumbuhan Ekspor Produk Primer Indonesia dengan Pendekatan Dekomposisi Shift Share - Aji, Sofyan (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2024)
Shift-Share analysis is a method to decompose total changes in economic indicators into various components/indicators which are sources of growth or decline. This analysis is used, among other things, to see economic growth through industrial mix components, and the competitiveness of labor in a region. By using decomposition analysis per component, this analysis can be applied to international trade analysis. This paper analyzes changes or